2019
DOI: 10.7554/elife.50925
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 5 (CDK5) regulates the circadian clock

Abstract: Circadian oscillations emerge from transcriptional and post-translational feedback loops. An important step in generating rhythmicity is the translocation of clock components into the nucleus, which is regulated in many cases by kinases. In mammals, the kinase promoting the nuclear import of the key clock component Period 2 (PER2) is unknown. Here, we show that the cyclin-dependent kinase 5 (CDK5) regulates the mammalian circadian clock involving phosphorylation of PER2. Knock-down of Cdk5 in the suprachiasmat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 77 publications
9
49
0
Order By: Relevance
“…Regulation of neurite outgrowth [54] Synaptic function Amphiphysin 1/S272, S276, S285 Increasing clathrin-mediated endocytosis [61,62] CaMKv/T345 Reducing spine density [71] Dynamin 1/S774, S778 Increasing clathrin-mediated endocytosis [62] Liprinα1/T701 Enhancing excitatory synaptic [69] Munc18/S158 Increasing vesicle release [60] NR2A/S1232 Regulation of synaptic plasticity [65,66] PSD-95/T19, S25, S35 Regulation of synaptic plasticity [67,69] SPAR/S1328 Regulation of synaptic homeostasis [75] TrkB/S478 Regulation of activity-dependent structural plasticity [70] L-VDCC/S783 Regulation of calcium influx [64] CaV2.2/S2013 Regulation of calcium influx [63] Circadian clock CLOCK/T451, T461 Promoting CLOCK nuclear translocalization and enhancing its activity [80] PER2/S394 Stabilizing PER2 and promoting its nuclear translocalization [79] Neurodegeneration…”
Section: -Ht6r/s350mentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of neurite outgrowth [54] Synaptic function Amphiphysin 1/S272, S276, S285 Increasing clathrin-mediated endocytosis [61,62] CaMKv/T345 Reducing spine density [71] Dynamin 1/S774, S778 Increasing clathrin-mediated endocytosis [62] Liprinα1/T701 Enhancing excitatory synaptic [69] Munc18/S158 Increasing vesicle release [60] NR2A/S1232 Regulation of synaptic plasticity [65,66] PSD-95/T19, S25, S35 Regulation of synaptic plasticity [67,69] SPAR/S1328 Regulation of synaptic homeostasis [75] TrkB/S478 Regulation of activity-dependent structural plasticity [70] L-VDCC/S783 Regulation of calcium influx [64] CaV2.2/S2013 Regulation of calcium influx [63] Circadian clock CLOCK/T451, T461 Promoting CLOCK nuclear translocalization and enhancing its activity [80] PER2/S394 Stabilizing PER2 and promoting its nuclear translocalization [79] Neurodegeneration…”
Section: -Ht6r/s350mentioning
confidence: 99%
“…Cdk5 has been implicated in the regulation of circadian clocks [ 79 , 80 ]. The running wheel test is a method to record circadian rhythm, whereby wild-type mice start wheel running precisely at the beginning of the dark phase.…”
Section: Roles Of Cdk5 In the Nervous Systemmentioning
confidence: 99%
“…Eventually PER proteins, along with CRY1 and CRY2, accumulate, then join to form a negative complex with CK1δ/ε, enter the nucleus, and block transcription activation by BMAL1/CLOCK (Lee et al, 2001;Okamura et al, 1999;Sato et al, 2006;Shearman et al, 2000). Recently, CDK5 was shown to phosphorylate PER2, promoting its association with CRY1 and their subsequent nuclear entry (Brenna et al, 2019). Although initially contested due to discrepant findings from several prior studies and unviability of Timmutant mice (Gotter, 2006), Barnes et al (2003) found that the full-length, but not truncated, isoform of TIM associates with PER proteins and forms part of the negative feedback loop in the molecular clock in the rat SCN (Barnes et al, 2003).…”
Section: Molecular Regulation Of Circadian Timingmentioning
confidence: 99%
“…Ultimately, all these binding cascades reduce the repressive histone methylation of the Cdk5 gene promoter by the cocaine-induced suppression of G9a [6,154,174,176]. Interestingly, Cdk5 was found to affect the circadian system indirectly through regulating other proteins that are involved in the clock mechanism (Per2) [178]. In contrast, with chronic amphetamine, ∆FosB was found to bind to its promoter and recruit several HDACs (HDAC1, SIRT1), inducing increased repressive histone methylation at this promoter perhaps related to G9a binding [171,174].…”
Section: Addiction and Epigeneticsmentioning
confidence: 99%